2013
DOI: 10.1111/gwat.12107
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Resistivity Characterization of Anisotropy in the Biscayne Aquifer

Abstract: Electrical anisotropy occurs when electric current flow varies with azimuth. In porous media, this may correspond to anisotropy in the hydraulic conductivity resulting from sedimentary fabric, fractures, or dissolution. In this study, a 28-electrode resistivity imaging system was used to investigate electrical anisotropy at 13 sites in the Biscayne Aquifer of SE Florida using the rotated square array method. The measured coefficient of electrical anisotropy generally ranged from 1.01 to 1.12 with values as hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 28 publications
1
11
0
2
Order By: Relevance
“…method is of particular interest because (i) numerous field, laboratory and theoretical studies have demonstrated that geoelectrical data are significantly affected by the presence and characteristics of fractures such as density, orientation and aperture (Taylor & Fleming 1988;Jinsong et al 2009); (ii) ER measurements can be acquired using a variety of electrode configurations and spacings, thereby offering the potential to obtain information on subsurface properties over a wide range of spatial scales (Telford et al 1990;Everett 2013); and (iii) strong analogies between fluid and electric current flow in fractured media suggest that geoelectrical data may contain important information regarding the corresponding hydrogeological properties (Brown 1989;Van Siclen 2002). As a result, ER studies in fractured rock have been widespread and include the development and application of anisotropic tomographic methods (Pain et al 2003;Herwanger et al 2004a,b;Li & Spitzer 2005;Greenhalgh et al 2009); the use of azimuthal resistivity surveys to estimate predominant fracture orientations (Taylor & Fleming 1988;Al Hagrey 1994;Lane et al 1995;Busby 2000) along with, in many cases, properties of the hydraulic conductivity tensor (Ritzi & Andolsek 1992;Skjernaa & Jørgensen 1994;Steinich & Marin 1996;Skinner & Heinson 2004;Boadu et al 2005;Boadu et al 2008;Yeboah-Forson & Whitman 2014) and the acquisition of surface-based electrical resistivity tomography (ERT) profiles for the identification and characterization of fracture zones (Porsani et al 2005;Sharma & Baranwal 2005;Yadav & Singh 2007;Robert et al 2011Robert et al , 2012.…”
Section: Introductionmentioning
confidence: 99%
“…method is of particular interest because (i) numerous field, laboratory and theoretical studies have demonstrated that geoelectrical data are significantly affected by the presence and characteristics of fractures such as density, orientation and aperture (Taylor & Fleming 1988;Jinsong et al 2009); (ii) ER measurements can be acquired using a variety of electrode configurations and spacings, thereby offering the potential to obtain information on subsurface properties over a wide range of spatial scales (Telford et al 1990;Everett 2013); and (iii) strong analogies between fluid and electric current flow in fractured media suggest that geoelectrical data may contain important information regarding the corresponding hydrogeological properties (Brown 1989;Van Siclen 2002). As a result, ER studies in fractured rock have been widespread and include the development and application of anisotropic tomographic methods (Pain et al 2003;Herwanger et al 2004a,b;Li & Spitzer 2005;Greenhalgh et al 2009); the use of azimuthal resistivity surveys to estimate predominant fracture orientations (Taylor & Fleming 1988;Al Hagrey 1994;Lane et al 1995;Busby 2000) along with, in many cases, properties of the hydraulic conductivity tensor (Ritzi & Andolsek 1992;Skjernaa & Jørgensen 1994;Steinich & Marin 1996;Skinner & Heinson 2004;Boadu et al 2005;Boadu et al 2008;Yeboah-Forson & Whitman 2014) and the acquisition of surface-based electrical resistivity tomography (ERT) profiles for the identification and characterization of fracture zones (Porsani et al 2005;Sharma & Baranwal 2005;Yadav & Singh 2007;Robert et al 2011Robert et al , 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Dentre os métodos geofísicos, o método elétrico de corrente contínua, baseado na medição da resistividade elétrica, permite o monitoramento da umidade do solo e a identificação do nível da água em aquíferos (Fetter, 1994). Esse método representa uma alternativa barata, não invasiva e simples de monitoramento geoelétrico da subsuperfície rasa (Loke, 2001;Ren e Tang, 2014;Yeboah-Forson et al, 2014).…”
Section: -Introduçãounclassified
“…Geophysical methods help us better understand fracture induced azimuthal anisotropy, specifically, 2D seismic refraction, and ER methods (Yeboah-Forson and Whitman, 2014;Busby, 2000;Zhu et al, 2012;Holbrook et al, 2014;Befus et al, 2011;Babcock et al, 2015;Greenhalgh et al, 2009;Matias, 2002;Li and Uren, 1997). Fracture presence introduces seismic azimuthal anisotropy (Tsvankin and Grechka, 2011;Lynn and Michelena, 2011;Burns et al, 2007;Crampin, 1985), and electrical azimuthal anisotropy (Berryman and Hoversten, 2013;Greenhalgh et al, 2010;Yeboah-Forson and Whitman, 2014;Taylor and Fleming, 1989).…”
Section: Importancementioning
confidence: 99%
“…Fracture presence introduces seismic azimuthal anisotropy (Tsvankin and Grechka, 2011;Lynn and Michelena, 2011;Burns et al, 2007;Crampin, 1985), and electrical azimuthal anisotropy (Berryman and Hoversten, 2013;Greenhalgh et al, 2010;Yeboah-Forson and Whitman, 2014;Taylor and Fleming, 1989). If hydraulic anisotropy exists in the subsurface, but is not taken into account, geophysical measurements can be interpreted incorrectly.…”
Section: Importancementioning
confidence: 99%
See 1 more Smart Citation